Study of mullerian anomalies over 5 years in a tertiary care centre - Antaratani, Ramalingappa C.; Kumar, Sanjana; Raju, Vinay (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Mullerian anomalies-developmental anomalies of the mullerian system might involve the uterus, cervix, fallopian tubes and vagina of which anomalies of the uterus are the most common. They are often regarded as a treatable form of infertility and have a prevalence of 0.5% in the general population. Though most of them remain asymptomatic, they contribute a good proportion of recurrent pregnancy losses, obstetric complications and infertility. Their timely diagnosis, management and evaluation of associated anomalies proves to be necessary. Methods: A prospective observational study was undertaken at KIMS, Hubli from 2014 to 2018. The study involved those women who were admitted in the department of obstetrics and gynecology at KIMS, Hubli for various reasons and were detected to have a mullerian anomaly. Their mode of presentation, method of detection, associated anomalies were analysed and statistical conclusions drawn from the same. Results: During the study period of 5 years, a total of 85 cases of mullerian anomalies were detected amounting to an incidence of 0.15%. 35% of them were asymptomatic, infertility (24%) being the next common mode of presentation. Septate/sub-septate uterus was found to have the poorest obstetric outcome. Mullerian anomalies were seen in combination in 14% of the cases and had an association with other anomalies like renal anomalies in 10% of the cases. Surgical correction was done for most of the cases of vaginal septum and septate/sub-septate uterus. Conclusions: Mullerian anomalies are often regarded as an uncommon but treatable form of infertility. Their timely detection, treatment and watchful obstetric management is in need.